Modulators of Networks: Molecular Targets of Arterial Calcification Identified in Man and Mice - Nitschke, Yvonne; Rutsch, Frank (Current Pharmaceutical Design, 2014)
In recent years, mechanisms of arterial calcifications are beginning to be elucidated. Arterial calcification is now considered as an actively regulated process resembling osteogenesis within the arterial wall orchestrated by a number of systemic or constitutively expressed mediators. Genetic studies of rare monogenic human disorders and studies of naturally occurring or mutant mouse models have identified specific inductors and inhibitors of arterial calcification, which can be classified according to the networks they participate in. These networks include ATP and pyrophosphate metabolism, phosphate homeostasis and vitamin D receptor signaling. Furthermore, intracellular signaling molecules, including SMAD6 and a number of systemic circulatory inhibitors of arterial calcification, including fetuin, tumor necrosis factor receptor superfamily member 11b, matrix GLA protein, adiponectin and family with sequence similarity 20 member A have been identified by human and mouse genetics. Based on the in vivo evidence of their functional relevance, these proteins will serve as excellent targets for the prevention and treatment of arterial calcification. In this review we discuss the functional role of the identified modulators of arterial calcification and describe the networks they belong to.
Keywords: PXE